Cartas del cielo = Letters from heaven - Gil, L. M. (Lydia M.), 1970- (Houston, Texas : Pinata Books, Arte Publico Press, 2014)
Celeste is heartbroken when her grandmother dies, but when letters and recipes begin to arrive with her grandmother's advice and recipes, Celeste finds consolation in preparing the dishes for herself, her mother, and their friends. Includes six traditional Cuban recipes.
Text in English and Spanish, bound together, back-to-back and inverted.
Keywords: Grief -- Juvenile fiction; Grandmothers -- Juvenile fiction; Cooking -- Juvenile fiction; Cuban Americans -- Juvenile fiction; Letters -- Juvenile fiction; Grief -- Fiction; Grandmothers -- Fiction; Cooking -- Fiction; Cuban Americans -- Fiction; Letters -- Fiction; Spanish language materials -- Bilingual; Upside-down books; Fiction; Upside-down books; Specimens